Gut Microbiome and Health Assessment Due To Arsenic Toxicity: A Review: Life Sciences-Arsenic Influence in Gut microbiome - Abhishek jain; Roshni jain; Swati jain; Subodh kumar jain; Swati singh thakur (International Journal of Life Science and Pharma Research, 2022)
Arsenic is considered as a class 1 carcinogen and first among toxicants ranked by the Environmental Protection Agency. Arsenic toxicity includes deleterious effect on gut microbiota, gastrointestinal disorder, immunological disturbances, disrupting metabolism and compromising the host health. Over 103–104 microorganisms with possibly 500 to 1,000 different species inhabit within the gut with 150 times more genes than the human genome. They help to digest food and play an essential role in our well- being. Gut microbiota affects our whole metabolism as well as the immune system of the host. Arsenic induced toxicity is a major health challenge leading to many neurological and immunological problems and inhibits the growth of many bacterial species common in the gastrointestinal tract. The Gut microbiome carries multiple functions that are beneficial to the hosts. Arsenic exposure will be a critical concern for human health. Human gut microbiomes may be biochemically responsible for arsenic metabolism, change in the arsenic compounds and several arsenical transformations that may lead to arsenic toxicity. Arsenic metabolism occurs in the liver by arsenic methyltransferase (AS3MT) which methylates it into the inorganic arsenic, and ultimately eliminated through urine. Recent studies showed that biotransformation of gut microbiome causes alteration of microbiome morphology and physiology that may alter the ArsBC gene activity due to arsenic toxicity. We aimed at summarising that arsenic induced perturbed gut microbiome communities that trigger systemic responses in diverse organs. Due to gut microbiota perturbation, changes in gut permeability and metabolism have been identified, and there is a shift in the population of gut bacterial species having arsenic resistant genes that result in disturbance of host metabolic homeostasis. Here we review known aspects of arsenic gut microbes' interaction, this will help to understand about arsenic toxicity with the gut microbiome and their deleterious effects.